Jinakost jako dekanonizace v poetice rané fáze české dekadentní poezii - Bednaříková, Hana (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2014)
The study deals with the specific context of the Czech poetry in the period of the mid-1890´s when the aesthetical and artistic conceptions of decadence as one of the progressive modernistic movements are established. This is the frame in which Jiří Karásek ze Lvovic and Arnošt Procházka published their early collections of poems. The aim of our analyses is to study and consider to which extent the Czech decadent poetry of the mid-1890´s represents inovations in artistic methods, topics, themes as a kind of diference and otherness in a general process of decanonization comparable to the European movement of the fin de sičcle modernism.
Keywords: Jiří Karásek ze Lvovic; Arnošt Procházka; poetics; semantic field; collections of poems; decadence; context of modernism